[es] OPTIMIZACION DE LA LOCALIZACION DE SOPORTES DE TUBERIAS - MARIA EUGENIA MOSCONI DE GOUVEA (2019)
[en] The present work is concerned with the optimal location of piping supports. A Weighted average of the stress resultants at specified points is used as the objective function to be minimized. ANSI piping codes are considered for the constrained functions. The minimization process is carried out using the conjugate gradient method on an interior penalty function. Numerical examples are presented at the end of the work.